Kajian Pemanfaatan Serat Alang-Alang Untuk Pembuatan Bata Ringan Berlobang - Suwarto, Suwarto; Isnadi, Isnadi; Hardono, Triatmo Sugih (Politeknik Negeri Semarang, 2011)
Brick is a building material used by most people as a couple walls. See its function as an insulator and not planned to support the weight of the walls are made of various materials such as masonry, brick pair, the pair of stone, wood boards, cubicles, plywood etc. The weeds are weeds and the weeds of agriculture because it is easy to grow and multiply rapidly, in many places especially fertile soil reaches a height of 1.0 to 2.0 meters. The total area of grasslands in Indonesia reaches ± 16 000 million hectares with a growth rate of approximately 200,000 hectares of which took place on an ongoing basis each year. This potential is neglected then used as a lightweight aggregate in the manufacture of building elements. Lightweight aggregate reed fibers can reduce the weight of concrete bricks, profits are easily obtainable. Lightweight brick reed fiber test results have an average length of 40.15 to 40.60 cm, a width of 18.83 to 19.35 cm and thickness from 10.08 to 10.23 cm, weight of 4373.25 to 7238, 25 grams lighter 20-50% by weight of cement concrete brick sand (the market). Compressive strength from 1.071 to 4.650 kg / cm ² does not qualify as low (class bricks of 25 kg / cm ²), while the brick with a mixture of Portland cement + sand as a comparison of eligible compressive strength class of 25 kg / cm ² is a mix of 1pc: 3 Ps and 1 Pc: 5 Ps. Regression values for light brick sand mixture 2 Y = 0.069 X ² - 1.0906 X + 5.4051 and the correlation R ² = 0.9388 has a strong relationship between the compressive strength with fiber content in a mixture of tall grass, on a mix of 3 sand Y = 0.0063 X ² + 0.1501 X - 3.3749 and the correlation R ² = 0.9592 has a strong relationship between the compressive strength with fiber content in the mixed grass. Reed fiber content higher compressive strong declining trend. High water absorption from 30.243 to 72.622 g / dm ² / min then a light brick to immersion in water first so that the species does not run out of water absorbed light brick. Lightweight brick low salinity <50% can be used in construction. Lightweight brick reed fibers can not be used for the construction of the walls that hold heavy loads and its use should be protected in place.